THE ANALYSIS OF LANGUAGE STYLE USED IN MERRY RIANA’S YOUTUBE CHANNEL ON THE PLAYLIST ‘SPOKEN WORD’ - Ester Febrina Br Sitepu; Ayuna Zahara; Ardhia Amalya Cahyani Putri; Rahmadsyah Rangkuti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
The aim of this study was to find out the types of language styles and identify the dominant style of language used by Merry Riana in her selected motivational speech videos as a motivator. The data of this study were taken from Merry Riana’s YouTube Channel and the researchers chose 3 motivational speech videos in the